#TITLE_ALTERNATIVE# - Christina Kaban (NIM 10103062), Lydia
ABSTRACT: In thermodynamics, entropy is known as a measure of disorder. It is an interesting subject that can be learned in mathematics, particularly in statistics. In this final thesis, several entropys characteristics in discrete and continoue random variable had been learned, such as the independence, marginal and conditional. Furthermore, entropy can be used for a case of special ditributions. Eventhough for several distributions, this thesis shows that the calculation of entropy will not be as simple as the calculation of the mean and the variation. This final thesis also study entropy in the sequence of random variable (stochastic process), especially in Markov chain and Hidden Markov Model (HMM). In HMM, entropy is used to locate the optimal state sequence in the model.